2014
DOI: 10.1093/heapro/dau095
|View full text |Cite
|
Sign up to set email alerts
|

Leadership skills are associated with health behaviours among Canadian children

Abstract: Life skills development is a core area for action in the Ottawa Charter for Health Promotion. The role of life skills in influencing health behaviours among children has received little attention in research. The purpose of this cross-sectional study was to investigate the relationship between self-leadership, as a model of life skills, and diet quality, physical activity, sleep duration and body weight. A provincially representative sample of 2328 grade 5 students (aged 10-11 years) was surveyed in Alberta, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…With an average DQII score of 58, the dietary quality of the children participating in the QUALITY study appeared slightly lower than that reported in prior studies that have used this measure. The DQII scores of 61 and 62 were observed for grade 5 students in the Canadian provinces of Nova Scotia ( 26 ) and Alberta ( 27 ) , respectively. Further, average DQII scores of 67, 60 and 59 have been reported for elementary students in Korea ( 28 ) and for nationally representative samples of children in China and the USA ( 17 ) , respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With an average DQII score of 58, the dietary quality of the children participating in the QUALITY study appeared slightly lower than that reported in prior studies that have used this measure. The DQII scores of 61 and 62 were observed for grade 5 students in the Canadian provinces of Nova Scotia ( 26 ) and Alberta ( 27 ) , respectively. Further, average DQII scores of 67, 60 and 59 have been reported for elementary students in Korea ( 28 ) and for nationally representative samples of children in China and the USA ( 17 ) , respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Age-and sex-specific dietary recommendations were used to calculate the DQII score (17,25) . The DQII has been used previously as a measure of dietary quality for children in Canada (26)(27)(28) , the USA (17) , China (17) and Korea (28) . It is a summary measure of dietary quality representing four categories of the diet, including variety, adequacy, moderation and overall balance.…”
Section: Dietary Qualitymentioning
confidence: 99%
“…Furthermore, we also miss the health benefits that may arise from improvements in knowledge of health, attitudes, self-efficacy and leadership that are also targeted by the APPLE Schools [5355]. Therefore, our estimates for the cost effectiveness ratio per QALY gained may be conservative.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding America, studies found in Canada and Nicaragua indicated that schoolchildren from 6 to 12 years old are physically active (Ferland et al, 2015;Khan et al, 2015;Reyes Ortiz et al, 2018;Voss et al, 2014). Nicaragua has been listed as one of the countries with the lowest human development index in the world (Programa de las Naciones Unidas para el Desarrollo, 2019), so these high levels could also be related to the aspects discussed in the paragraph above by the economic and human development factors.…”
Section: Discussionmentioning
confidence: 99%
“…Table 3 shows the characteristics of the studies found during the searching, including author/s, year of publication, sample size and age, and the results on the level of selfreported PA; both globally, and stratified by gender or body status, whenever possible. In total, we included 23 studies in the review: eight in Europe (four from Spain, three from England and one from Switzerland) (Arriscado et al, 2015;Benítez-Porres et al, 2016a, 2016bGarcía-Cervantes et al, 2016;Sandercock & Cohen, 2019;Schmidt et al, 2017;Voss et al, 2014); eight in Asia (three in Iran, three in Malaysia and two in China) (Chan et al, 2019;Firouzi et al, 2014;Guo & Wang, 2017;Jan Mohamed et al, 2015;Keykhaei et al, 2016;Khodaverdi & Bahram, 2015;Rostami-Moez et al, 2017;Thien et al, 2015); six in America (three in Canada, one in the US, one in Brazil and one in Nicaragua) (Brown et al, 2018;Silva & Cavalcante Neto, 2017;Ferland et al, 2015;Khan et al, 2015;Reyes Ortiz et al, 2018;Voss et al, 2014); and one in Africa (Mauritius) (Bundhun et al, 2018). However, the cross-cultural study by Voss et al (2014) was carried out in both America (Canada) and Europe (England); including the results of two samples in the same research work.…”
Section: Risk Of Individual Bias In the Studiesmentioning
confidence: 99%